Vegetation structure, biomass, and carbon of Mangrove Forests in Ambon Bay, Maluku, Indonesia - Kaimuddin, Muhammad Irfan; Kusmana, Cecep; Setiawan, Yudi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Mangrove forests serve a substantial part in coastal areas as high-carbon-storage woody vegetation ecosystems that grow on muddy and anaerobic soils. This study determined the species composition and estimated the biomass production and storage of carbon in Ambon Bay mangrove forests. Vegetation surveys for species composition were conducted using the square plot technique by making standard observation plots for density, frequency, dominance, and important value index data analysis. We used Allometric equations and the Loss-on-ignition method to calculate the biomass and soil carbon. Vegetation surveys revealed eight species of tree-habitus mangroves, and Sonneratia alba was a mono-dominant species with an important value index of more than 100%. The study revealed the highest average potential of biomass and carbon in Passo Village with AGB 280.47±168.94 Mg ha-1, BGB 83.06±55.1 Mg ha-1, and sediment carbon 320.03±106.97 Mg C ha-1. The carbon stock of the mangrove forest in Ambon Bay was estimated at 400.67±166.25 Mg C ha-1. We conclude that mangrove forest carbon stores in Ambon Bay had relatively high values. Passo Village has the largest carbon store compared to other locations in the Ambon Bay mangrove forest.